73.5k views
1 vote
V=u-3t (t)

Help me asap..
i want step by step explanation ^_^​

User Glori
by
5.2k points

2 Answers

4 votes

Answer: t = -v/3 + u/3

Step-by-step explanation:

v = u - 3t

1. Subtract u from both sides

v - u = u -3t - u

v - u = -3t

2. Divide -3 from both sides to isolate the t

(v - u) / -3 = -3t / -3

3. Simplify

-v/3 + u/3 = t

User Nicolas Castro
by
4.8k points
5 votes

Answer:


t = -(v - u)/(3)

Explanation:

Hello!

Solve the literal equation by t by isolating the variable.

What is a Literal Equation?

A literal equation is an equation consisting of only or primarily variables, with coefficients.

Solve for t


  • v = u - 3t

  • v - u = -3t

  • -(v - u)/(3) = t

The solution for t is
-(v - u)/(3).

User Fhd
by
4.6k points